Developing Moderate Islamic Education: Special Reference to Al-Daghasyi’s Thought and Its Contextualization in Indonesia - Sabarudin Sabarudin; Mahmud Arif; Zainudin Zainudin; Akhyak Akhyak; Mirna Guswenti; Rafidah Abdullah (International Journal of Educational Narratives, 2025)
Background. One of the main agendas for promoting a harmonious life in a diverse society strengthening religious moderation, which has become a priority program of the government. The agenda for enhancing religious moderation should receive widespread attention from intellectuals in this country as part of their commitment to addressing the serious threat of intolerance and extremism: radicalism and liberalism. Purpose. This study tries to contribute to the reinforcement of religious moderation through literary explorations concerning the concept of moderate Islamic education. Considering that many similarities in the context of the dynamics of actual problems in this country with those, national and global as reflected in al-Daghasyi’s thoughts Method. This research was a study of al-Daghasyi’s educational thoughts through literary explorations which were then positioned as a dialogue partner to formulate the significant concept for the development of moderate Islamic education. The thoughts were contextualized with the reality in Indonesia. Results. According to al-Daghasyi, when education is based on moderate Islam, it will play an important role in preventing deviant attitudes and behaviours, such as intolerance and extremism, namely al-ifr?th and al-tafrîth (liberalism and radicalism). al-Daghasyi states that issues in Islam that cause differences of opinion among Muslims and do not trigger conflict and hostility can be considered religious issues. Conclusion. This study has significant implications for instructional practices in The real endeavor does not involve weapon confrontations but fundamentally deals with preventing warfare and injustice through peaceful means, especially moderate Islamic education.